A method for producing concrete by using recycled concrete and boiler bottom slag
By rationally treating and mixing the recycled concrete with the CFB boiler slag, a concrete material with excellent performance is prepared, which solves the problems of resource depletion and waste treatment, and achieves the dual benefits of environmental protection and economic benefits.
Patent Information
- Application Number
- CN202411667024.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing concrete production methods rely on natural river sand and stone, resulting in resource depletion and increased production costs. At the same time, the problems of handling construction waste and CFB boiler slag have not been effectively solved.
By screening, crushing and alkali-exciting the recovered concrete with CFB boiler slag, mixing reasonably, carbonizing and drying, concrete materials with excellent performance are prepared.
Reuse of resources has been achieved, emissions of construction waste and CFB slag have been reduced, concrete production costs have been reduced, and it has good environmental protection and economic benefits.
Smart Images

Figure CN119143457B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource recycling and building material preparation, and in particular to a preparation method for producing concrete by utilizing recycled concrete and boiler bottom slag. Background Art
[0002] CFB boiler slag refers to the solid waste generated after the circulating fluidized bed is burned. The annual CFB slag emission in my country has exceeded 100 million tons. Natural stacking not only occupies land, but also pollutes the environment. If this part of CFB slag can be reasonably utilized, it can not only deal with this part of waste, but also generate considerable economic benefits. For a long time, the municipal and infrastructure projects in my country have been in full swing. In the process of building and demolishing municipal and infrastructure projects, a large amount of construction waste has also been generated. At present, my country's construction waste has accounted for 40% of urban waste, and waste concrete has exceeded 23%. More than 70% of the materials of waste concrete are aggregates, which mainly need to be obtained through mountain excavation and processed into sand and gravel, or directly dig river silt, pebbles, etc. to make concrete, but natural resources are exhausted. In the existing concrete production methods, aggregates are mostly derived from the mining of natural river sand and stone, which gradually leads to the depletion of natural resources. With the strengthening of environmental protection policies, mining is restricted, and the production cost of concrete continues to rise.
[0003] CFB boiler slag can replace machine-made sand. As a new type of concrete material, waste concrete can also be reused through crushing and grading. Therefore, a preparation method for producing concrete using recycled concrete and boiler bottom slag is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a new concrete preparation method, by reasonably mixing recycled concrete with CFB boiler slag, and then undergoing a series of treatment processes, to prepare a concrete material with excellent performance. This method can not only reduce the discharge of construction waste and CFB slag, but also effectively reduce the cost of concrete production, save natural resources, and have good environmental protection and economic benefits. In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0005] A method for preparing concrete produced by using recycled concrete and boiler bottom ash, comprising the following steps:
[0006] Step 1: Screening of CFB boiler slag: Screening of CFB boiler slag to select particles with a particle size of 0.15-4.75 mm and remove large particles and impurities;
[0007] Step 2: Crushing and screening of waste concrete. Crushing waste concrete, and performing multi-stage screening treatment. After initial crushing, large particles are crushed into particles with a particle size of 5-25 mm, which are recycled as aggregates and screened again to obtain old mortar residues. The particle size of the old mortar residues is ≤0.15 mm.
[0008] Step 3: Mixed alkali excitation treatment, mix CFB boiler slag and old mortar residue in a mass ratio of 3:1 and put them into the reactor, add 5%-8% NaOH solution to keep the liquid-solid ratio at 0.4-0.6, react for 2-3h, the reaction temperature is 60-80℃, keep uniform stirring, and the stirring rate is 100-200rpm;
[0009] Step 4: Filtration and drying: After the reaction, filter out the residual solution and dry the mixture. The drying temperature is controlled to be 80-100°C for 2-4 hours to obtain a dry powdered active material.
[0010] Step 5: Wetting treatment: mix the powdered active material and the waste concrete aggregate in a mass ratio of 4:5-5:4, add lime water for wetting treatment, control the water-to-solid ratio at 0.15-0.20, and control the wetting time at 30-60 minutes;
[0011] Step 6: Carbonization reaction: Place the mixed and moistened materials in a sealed environment and continuously introduce carbon dioxide gas, maintaining the concentration of carbon dioxide at 5-10% for 1-3 hours;
[0012] Step 7: Low temperature drying after carbonization: the carbonized material is placed in a low temperature drying at 50-80℃ for 3-6h;
[0013] Step 8: Add 0.5%-1.0% polycarboxylate water reducer, 0.1%-2% anticorrosive, 5%-8% sulphoaluminate-based expansion agent, 0.002%-0.01% rosin resin air entraining agent to the total mass of concrete; add 10-15% fly ash and / or slag powder to the total mass of the mixture, add 20-30% cement to the total mass of the mixture, and control the water-cement ratio to 0.35-0.40;
[0014] Step 9: Continue mechanical stirring, using mechanical stirring equipment, stirring for 5-10 minutes;
[0015] Step 10: Molding and Vibrating Pour the mixed concrete slurry into the formwork and vibrate it with a vibrator for 30-60 seconds.
[0016] Preferably, for humid and high-salinity areas, the powdered active material is mixed with waste concrete aggregate in a 1:1 mass ratio.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] The present invention utilizes recycled concrete and CFB boiler slag as main raw materials, greatly reducing the emission of construction waste and industrial waste, and simultaneously produces high-strength and durable concrete materials through reasonable chemical reaction and physical treatment. By fully activating and carbonizing the calcium oxide in the old mortar residue and slag, the prepared concrete not only has good mechanical properties, but also can effectively reduce the production cost, and has significant environmental protection and economic benefits. The composite use of CFB slag and treated RCA can further optimize the performance of concrete, especially in terms of environmental adaptability and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A schematic flow chart of a method for producing concrete by using recycled concrete and boiler bottom ash proposed by the present invention;
[0020] Figure 2 This is a CFB slag XDR spectrum of a preparation method for producing concrete using recycled concrete and boiler bottom ash proposed by the present invention;
[0021] Figure 3 This is a graph showing the change in consistency loss over 180 minutes for groups I, II and III in an embodiment of a method for producing concrete using recycled concrete and boiler bottom ash proposed in the present invention. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0023] Reference Figure 1-2 CFB slag contains a high content of calcium sulfate, which can be further hydrated in concrete to form products such as calcium aluminate, which helps to improve the concrete's resistance to sulfate erosion. Carbonization treatment can seal the pores in the waste concrete and reduce its water absorption rate, thereby improving the compressive strength and durability of the waste concrete.
[0024] Reference Figure 1 , a concrete produced using recycled concrete and boiler bottom slag, the main components of which include CFB boiler slag, recycled concrete aggregate, recycled concrete old mortar residue, cement, water reducing agent, corrosion inhibitor, expansion agent and air entraining agent.
[0025] A method for preparing concrete produced by using recycled concrete and boiler bottom ash comprises the following steps:
[0026] Step 1: Screening of CFB boiler slag: Screening of CFB boiler slag to select particles with a particle size of 0.15-4.75 mm and remove large particles and impurities;
[0027] Optionally, use a vibrating screen or drum screen to remove large particles and impurities with a particle size greater than 4.75 mm, set the amplitude to 2-5 mm, and the frequency to 50-100 Hz. The amplitude and frequency are adjusted according to the characteristics of different CFB boiler slags. Pour the slag evenly into the vibrating screen, and the equipment will automatically vibrate and screen for 15-30 minutes. The large particles and impurities are screened out, collected and processed, and the screened material enters the next step;
[0028] Use multi-layer screening equipment for step-by-step screening, 0.15mm-4.75mm multi-level screening, two layers of screens, the first layer is 4.75mm, the second layer is 0.15mm, the vibration frequency is 100-200Hz, and the screening time is 20-40min; the oversize (>4.75mm) and undersize (<0.15mm) are recovered and processed separately, and qualified particles are retained;
[0029] Optionally, the screened slag is passed through a magnetic separator or the magnetic metal material is removed, and the magnetic separation is performed for 10-15 minutes, and the magnetic field strength is 500-1500 Gauss; a wind separator is used to blow away light impurities, unburned coal powder, etc., and the wind separation process is 10-20 minutes, and the wind speed is set to 2-4m / s;
[0030] Optionally, use a wet screening machine to remove dust and water-soluble impurities attached to the surface of the slag, use a room temperature water source, 100-300L / min water washing for 10-20min, use a rotary dryer to dry for 30-60min, the drying temperature is 50-80℃, and the moisture content of the slag is checked regularly. Stop drying when the target is reached. The target moisture content is controlled at 1%-3%.
[0031] Step 2: Crushing and screening of waste concrete. Crushing waste concrete, and performing multi-stage screening treatment. After initial crushing, large particles are crushed into particles with a particle size of 5-25 mm, which are recycled as aggregates and screened again to obtain old mortar residues. The particle size of the old mortar residues is ≤0.15 mm.
[0032] Obvious impurities and foreign matter such as steel bars, wood, and plastic in the waste concrete are removed manually or mechanically, and oversized concrete blocks (greater than 500mm) are pre-crushed to a size that can enter the crushing equipment using a breaker or hydraulic shear;
[0033] In the initial crushing, for large pieces of concrete waste, a jaw crusher is used to crush the concrete into smaller pieces through extrusion. The feed port size of the jaw crusher is set to 500-1200mm. The large pieces of concrete waste are placed in the jaw crusher, and the discharge port size is adjusted to control the particle size after crushing to 20-100mm. For medium-hard concrete waste, an impact crusher is used to crush the concrete through impact force.
[0034] The crushed concrete particles are screened to separate the large aggregate particles and small old mortar residue particles that meet the requirements. First, a larger aperture screen (25mm) is used, and then a smaller aperture screen (5mm) is used for classification. The vibration frequency is set to 100-200Hz, the amplitude is 2-5mm, and the vibration screening is 20-40min; the first layer screens out particles larger than 25mm, these large particles enter the secondary crushing, and the second layer screens out particles with a particle size of 5-25mm, which are recycled as aggregates. Particles smaller than 5mm (including old mortar residues) will enter the subsequent steps.
[0035] Step 3: Mixed alkali excitation treatment, mix CFB boiler slag and old mortar residue in a mass ratio of 3:1 and put them into the reactor, add 5%-8% NaOH solution to keep the liquid-solid ratio at 0.4-0.6, react for 2-3h, the reaction temperature is 60-80℃, keep uniform stirring, and the stirring rate is 100-200rpm;
[0036] The old mortar residue has high water absorption and low activity. Through pre-immersion in lime water and carbonization, a layer of calcium carbonate can be formed on the surface of the old mortar residue, which effectively improves the strength of the old mortar and improves the bonding between the new and old matrices. CFB slag contains a high content of calcium sulfate, which can be further hydrated in concrete to form products such as calcium sulfate, which may help improve the concrete's resistance to sulfate erosion. However, it is also necessary to pay attention to the impact of calcium sulfate on the durability of concrete in long-term use.
[0037] To this end, alkali activation treatment is performed on CFB boiler bottom ash and old mortar residues. Alkali activation can activate the active ingredients in these two materials, making them play a role similar to mineral admixtures in the cement matrix, thereby enhancing the mechanical properties and durability of concrete. Calcium sulfate in CFB boiler bottom ash and calcium silicate in old mortar residues will form more active calcium silicate hydration products (such as CSH gel). This combined treatment method combines the material treatment steps that originally needed to be performed separately, reduces the process flow, reduces production costs, and improves treatment efficiency. It not only effectively utilizes industrial waste, but also reduces the generation of wastewater and harmful substances, which helps promote the application of green building materials.
[0038] Step 4: Filtration and drying: After the reaction, filter out the residual solution and dry the mixture. The drying temperature is controlled to be 80-100°C for 2-4 hours to obtain a dry powdered active material.
[0039] It should be noted that alkali activation treatment may leave some alkaline substances, which may affect the long-term durability of concrete in subsequent use. Therefore, cleaning operations can be added before drying according to the amount of NaOH solution used.
[0040] Step 5: Wetting treatment: mix the powdered active material and the waste concrete aggregate in a mass ratio of 4:5-5:4, add lime water for wetting treatment, control the water-to-solid ratio at 0.15-0.20, and control the wetting time at 30-60 minutes;
[0041] It should be noted that the wetting time needs to be sufficient to allow the free calcium oxide in the CFB slag to fully react with water to form calcium hydroxide, and the RCA surface begins to absorb moisture. The moisture content of the material after wetting treatment needs to be maintained at 5%-7%, and excessive wetting or drying must be prevented to affect the carbonization reaction.
[0042] Step 6: Carbonization reaction: Place the mixed and moistened materials in a sealed environment and continuously introduce carbon dioxide gas, maintaining the concentration of carbon dioxide at 5-10% for 1-3 hours;
[0043] Specifically, the moistened mixed material is placed in a sealed reaction chamber, and CO2 gas is continuously introduced to ensure that the concentration of carbon dioxide is controlled at 5%-10%, and the reaction time is controlled at 1-3 hours. Depending on the size of the sealed space, the gas flow rate can be set at 0.5-1.5L / min, and the pH value changes or material surface hardening during the carbonization process are monitored in real time to determine whether the carbonization reaction is sufficient.
[0044] Step 7: Low temperature drying after carbonization: the carbonized material is placed in a low temperature drying at 50-80℃ for 3-6h;
[0045] Specifically, hot air drying equipment or infrared drying machine is used for drying, the drying temperature is controlled at 50-80℃, the drying time is 3-6h, and excessive evaporation of water should be prevented during the drying process to ensure that the material does not become brittle, but at the same time, the moisture content of the dried material needs to be maintained at 2%-3% for subsequent mixing.
[0046] Step 8: Add 0.5%-1.0% polycarboxylate water reducer, 0.1%-2% anticorrosive, 5%-8% sulphoaluminate-based expansion agent, 0.002%-0.01% rosin resin air entraining agent to the total mass of concrete; add 10-15% fly ash and / or slag powder to the total mass of the mixture. Specifically, the amount of fly ash needs to be adjusted according to the specific concrete design requirements and environmental conditions. For projects with high durability requirements, especially concrete exposed to sulfate or chloride environments, the amount of slag powder can be appropriately increased, adding 20-30% of cement to the total mass of the mixture, and the water-cement ratio is controlled at 0.35-0.40;
[0047] Specifically, first pour the powdered active material, fly ash and / or slag powder, cement, expansion agent, and corrosion inhibitor into a mixer, and perform dry mixing for 1-2 minutes to ensure that the expansion agent and corrosion inhibitor are evenly distributed in the concrete. Then add a specified amount of water to the mixer, and add a water reducer and an air entraining agent at the same time. The admixture can be mixed with water in advance and then added, or it can be directly added during the mixing process in water, and wet mixing is performed for 3-5 minutes.
[0048] Step 9: Continue mechanical stirring, using mechanical stirring equipment, stirring for 5-10 minutes.
[0049] Step 10: Molding and Vibration Pour the mixed concrete slurry into the formwork and vibrate it with a vibrator for 30-60 seconds to expel the bubbles in the concrete, ensuring that the formwork is clean and flat to avoid adhesion of the slurry.
[0050] Example
[0051] The climate in coastal cities is humid and the air contains a lot of salt. Concrete structures are easily corroded by chloride ions, which causes steel bars to rust, thereby affecting the durability of buildings. This embodiment adjusts the concrete formula to enhance its salt corrosion resistance and durability, and is suitable for building structures in coastal cities.
[0052] Raw materials:
[0053]
[0054] The CFB boiler slag is screened to 0.15-4.75 mm, large particles and impurities are removed, the waste concrete is crushed and screened to obtain aggregate with a particle size of 5-25 mm and old mortar residues ≤ 0.15 mm, the screened CFB boiler slag, waste concrete aggregate and old mortar residues are mixed in a ratio of 4:5-5:4, 15% of silica fume and slag powder, cement and 1% of polycarboxylate water reducer are added, the water-cement ratio is 0.35, and the mixture is evenly stirred for 5-10 minutes to form a mixture, and lime water is added to wet the mixture. Moisten the mixture with a water-to-solid ratio of 0.2 for 30 minutes to ensure that the surface of the material absorbs moisture evenly, add 2% of silicone waterproofing agent, place the moistened mixed material in a sealed environment, and introduce 5%-10% carbon dioxide gas for 2 hours to carry out carbonization reaction to generate calcium carbonate to improve structural stability. During the stirring process, 1.5% of calcium nitrite rust inhibitor is continuously and slowly added to prevent chloride ion corrosion on the steel bars. Finally, pour the mixed slurry into the formwork, vibrate it with a vibrator for 60 seconds, and carry out natural curing after molding.
[0055] The powdered active material was mixed with waste concrete aggregate in a mass ratio of 4:5, 5:4, and 1:1, and recorded as Groups I, II, and III, respectively. The 3h mortar consistency loss rate of the three groups of concrete was calculated.
[0056] (1)
[0057] Reference Figure 3 , calculated using formula (1), where is the initial consistency, is the consistency value at the nth minute, r is the consistency loss rate;
[0058] The proportion of Group I is biased towards waste concrete aggregates, with a higher content of waste concrete aggregates and relatively less powdered active materials. Due to the limited water absorption capacity of aggregates, the initial consistency is good, but as time goes by, the consistency loss is faster, especially after 120 minutes, the consistency loss rate accelerates, and the loss rate reaches the highest at 180 minutes. The proportion of powdered active materials in Group II increases, which enhances the water retention and consistency maintenance capabilities of concrete. Therefore, the consistency loss is slower, which is much less than that of the 4:5 ratio. Group III has the best consistency maintenance performance when the powdered active materials and waste concrete aggregates are balanced. Since the effects of the two are balanced, the consistency loss rate is the lowest. The occurrence of this situation may also be related to the water-cement ratio.
[0059] Compressive strength tests were carried out on groups I, II and III. Concrete samples of each mix ratio were made into cubic test blocks according to standard size (150mmx150mmx150mm). The cement content remained unchanged, and the water-cement ratio was 0.35. The ratio of cement to water was controlled to ensure that the fluidity of concrete with different mix ratios was consistent. After the concrete test blocks were cast, they were cured under standard curing conditions (20℃, relative humidity 95%) for 7 days, 28 days and 90 days of strength tests.
[0060] The compressive strength test of concrete blocks with different curing times was carried out by a standard pressure testing machine in accordance with GB / T50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The test results are as follows:
[0061]
[0062] At 7 days, the compressive strength of different mixes was not much different, but the 1:1 mix showed the highest early strength of 28.34 MPa, while the 4:5 mix showed a relatively low compressive strength. The difference in early strength was mainly related to the ratio of powdered active materials to aggregates. A higher ratio of powdered active materials can increase the early hydration reaction rate and increase the initial strength. 28 days is the standard time point for concrete strength testing. At this time, the compressive strength of different mixes is further differentiated. The compressive strength of the 1:1 mix is about 10% higher than that of the 4:5 mix. The 5:4 mix is 36.12 MPa, which also shows good mechanical properties. The higher ratio of powdered active materials can significantly enhance the generation of hydration products and increase the density and strength of concrete. At 90 days, the strength of all samples is further improved, but the increase is small. From the perspective of long-term strength performance, concrete with a high ratio of powdered active materials shows better strength development. A higher ratio of powdered active materials increases the density of concrete and reduces porosity, thereby enhancing the durability and compressive resistance of concrete.
[0063] The strength test results show that the 1:1 ratio of concrete shows the best mechanical properties in different time periods and is suitable for construction projects that require high strength and long life. The 5:4 ratio also has good performance and is suitable for projects that do not require high early strength but require long-term strength development.
[0064] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing concrete produced by using recycled concrete and boiler bottom ash, characterized in that: The following steps are involved: Step 1: Screening of CFB boiler slag: Screening of CFB boiler slag to select particles with a particle size of 0.15-4.75 mm and remove large particles and impurities; Step 2: Crushing and screening of waste concrete. Crushing waste concrete, and performing multi-stage screening treatment. After initial crushing, large particles are crushed into particles with a particle size of 5-25 mm, which are recycled as aggregates and screened again to obtain old mortar residues. The particle size of the old mortar residues is ≤0.15 mm. Step 3: Mixed alkali excitation treatment, mix CFB boiler slag and old mortar residue in a mass ratio of 3:1 and put them into the reactor, add 5%-8% NaOH solution to keep the liquid-solid ratio at 0.4-0.6, react for 2-3h, the reaction temperature is 60-80℃, keep uniform stirring, and the stirring rate is 100-200rpm; Step 4: Filtration and drying: After the reaction, filter out the residual solution and dry the mixture. The drying temperature is controlled to be 80-100°C for 2-4 hours to obtain a dry powdered active material. Step 5: Wetting treatment: mix the powdered active material and the waste concrete aggregate in a mass ratio of 4:5-5:4, add lime water for wetting treatment, control the water-to-solid ratio at 0.15-0.20, and control the wetting time at 30-60 minutes; Step 6: Carbonization reaction: Place the mixed and moistened materials in a sealed environment and continuously introduce carbon dioxide gas, maintaining the concentration of carbon dioxide at 5-10% for 1-3 hours; Step 7: Low temperature drying after carbonization: the carbonized material is placed in a low temperature drying at 50-80℃ for 3-6h; Step 8: Add 0.5%-1.0% polycarboxylate water reducer, 0.1%-2% anticorrosive, 5%-8% sulphoaluminate-based expansion agent, 0.002%-0.01% rosin resin air entraining agent to the total mass of concrete; add 10-15% fly ash and / or slag powder to the total mass of the mixture, add 20-30% cement to the total mass of the mixture, and control the water-cement ratio to 0.35-0.40; Step 9: Continue mechanical stirring, using mechanical stirring equipment, stirring for 5-10 minutes; Step 10: Molding and Vibrating Pour the mixed concrete slurry into the formwork and vibrate it with a vibrator for 30-60 seconds.
2. The method for preparing concrete produced by using recycled concrete and boiler bottom ash according to claim 1, characterized in that: For humid and high-salinity areas, the powdered active material is mixed with waste concrete aggregate in a 1:1 mass ratio.
Citation Information
Patent Citations
Circulating fluidized bed slag reinforced modification method and application thereof
CN114057419A